The Regional Analysis of Beef Cattle Farm Development in Semarang Regency - B. Santoso; B. W. H. E. Prasetiyono (Tropical Animal Science Journal, 2020)
One of the reasons for the low production and productivity of beef cattle in Indonesia is that information on the allocation of livestock areas development is not yet clear. This study aimed to determine the priority areas for developing beef cattle farm in Semarang Regency based on the concept of sustainability. Sustainability was analyzed through the determination of leading commodities (analysis of Location Quotient and Shift Share), optimization of regional potential (analysis of carrying capacity and carrying capacity index of forage, and assessment of suitability of ecological environment of beef cattle). The process of spatial analysis used GIS software. Comprehensive planning for the development of beef cattle farm was directed in three sub-districts, namely: Bringin, Bancak, and Banyubiru. The results of the analysis showed that the three sub-districts were beef cattle base areas (LQ>1), had business growth (positive SS), and had a safe status for forage availability (>2). Other results showed that the carrying capacity for beef cattle farms in Bringin sub-district was 15,829 AU, Bancak was 8,457 AU, and Banyubiru was 6,315 AU. The land area suitable for beef cattle farm from the three priority sub-districts was 5,760.141 Ha. It can be concluded that the development of beef cattle farm in Semarang Regency is focused on three priority sub-districts, namely: Bringin, Bancak, and Banyubiru. The results of this study can be an input for local governments in determining the direction and pattern of beef cattle farm development to be more sustainable.